SOA with Java : realizing service-orientation with Java technologies - Erl, Thomas (Service Tech Press, 2014)
"An outstanding depth-and-breadth resource for IT architects and Java professionals to understand and apply the marriage of SOA and modern Java." -- Antonio Bruno , Enterprise Architecture and Strategy, digitalStrom "A great self-contained book on SOA using flexible Java implementations...." -- Roger Stoffers , Hewlett Packard "Provides clarity on abstract concepts and is filled with concrete examples of implementing SOA principles in Java environments." -- Sanjay Singh , Certified SOA Architect "...provides a holistic, comprehensive view on leveraging SOA principles and architecture for building and deploying performant Java services." -- Suzanne D'Souza , KBACE Technologies "Thomas Erl's series of books on services technology have shaped, influenced, and strengthened a whole community of enterprise and solution architects' thinking and solution development, and the much awaited SOA with Java book is an excellent addition to the series. It is a must-read." -- Lalatendu Rath , Wipro Technologies The Definitive Guide to Building Service-Oriented Solutions with Lightweight and Mainstream Java Technologies Java has evolved into an exceptional platform for building Web-based enterprise services. In SOA with Java , Thomas Erl and several world-class experts guide you in mastering the principles, best practices, and Java technologies you need to design and deliver high-value services and service-oriented solutions. You'll learn how to implement SOA with lightweight frameworks, mainstream Java services technologies, and contemporary specifications and standards. To demonstrate real-world examples, the authors present multiple case study scenarios. They further demystify complex concepts with a plain-English writing style. This book will be valuable to all developers, analysts, architects, and other IT professionals who want to design and implement Web-based service-oriented architectures and enterprise solutions with Java technologies. Topic Areas Applying modern service-orientation principles to modern Java technology platforms Leveraging Java infrastructure extensions relevant to service-oriented solutions Exploring key concepts associated with SOA and service-orientation within the context of Java Reviewing relevant Java platforms, technologies, and APIs Understanding the standards and conventions that REST and SOAP services are built upon in relation to Java implementations Building Java Web-based services with JAX-WS and JAX-RS Applying...